Your emotion or mine: labeling feelings alters emotional face perception—an ERP study on automatic and intentional affect labeling - Herbert, Cornelia; Sfaerlea, Anca; Blumenthal, Terry (Frontiers in Human Neuroscience, 2013)
Empirical evidence suggests that words are powerful regulators of emotion processing. Although a number of studies have used words as contextual cues for emotion processing, the role of what is being labeled by the words (i.e. one’s own emotion as compared to the emotion expressed by the sender) is poorly understood. The present study reports results from two experiments which used ERP methodology to evaluate the impact of emotional faces and self- versus sender-related emotional pronoun-noun pairs (e.g. my fear vs. his fear) as cues for emotional face processing. The influence of self- and sender-related cues on the processing of fearful, angry and happy faces was investigated in two contexts: an automatic (experiment 1) and intentional affect labeling task (experiment 2), along with control conditions of passive face processing. ERP patterns varied as a function of the label’s reference (self vs. sender) and the intentionality of the labelling task (experiment 1 vs. experiment 2). In experiment 1, self-related labels increased the motivational relevance of the emotional faces in the time-window of the EPN component. Processing of sender-related labels improved emotion recognition specifically for fearful faces in the N170 time-window. Spontaneous processing of affective labels modulated later stages of face processing as well. Amplitudes of the late positive potential (LPP) were reduced for fearful, happy, and angry faces relative to the control condition of passive viewing. During intentional regulation (experiment 2) amplitudes of the LPP were enhanced for emotional faces when subjects used the self-related emotion labels to label their own emotion during face processing, and they rated the faces as higher in arousal than the emotional faces that had been presented in the “label sender’s emotion” condition or the passive viewing condition. The present results argue in favor of a differentiated view of language-as-context for emotion processing.